EKSISTENSI KAPAL KAYU: DALAM MENGARUNGI LAUT BEBAS DAN PERUBAHAN ZAMAN - Andi Nuralang (Naditira Widya, 2009)
Ships of wood are one of the many water transportations which suffer the cultural-economic impact on the use of vessels. Despite it capability to cross the vast oceans and face the change of time, its existence depends on human’s decision to continuously preserve its cultural identity or completely replace wooden ships with modern ones. Nevertheless, such traditional vessels still can be seen even among the modern society. This article discusses the utilizing of wooden ships for sailing the ocean and its existence through time changes.